The challenge of major games for centre operations - Lowry, M. (4. International Forum on Elite Sport. Montreal, Canada, 26-28 July 2005, 2005)
Own the podium - What were the gaps? • Performance Enhancement Teams: Sport Science, athlete testing, medical • Talent ID and recruitment • Top Secret 2010: Research and Innovation • National Sport Federation Support - Athletes; Coaches, Competitions • Olympic Games Preparation (specialization for performance!)